Androgen receptor activation decreases proliferation in thyroid cancer cells. Issue 9 (20th April 2021) - Jones, Melanie E.; O'Connell, Timmy J.; Zhao, Hong; Darzynkiewicz, Zgibniew; Gupta, Anvita; Buchsbaum, Joseph; Shin, Edward; Iacob, Codrin; Suslina, Nina; Moscatello, Augustine; Schantz, Stimson; Tiwari, Raj; et al.
Abstract: The American Cancer Society predicted more than 52 000 new cases of thyroid cancer in 2020, making it the most prevalent endocrine malignancy. Due to the approximately threefold higher incidence of thyroid cancer in women, we hypothesize that androgens and/or androgen receptors play a protective role and that thyroid cancer in men represents an escape from androgen‐mediated cell regulation. The analysis of androgen receptor (AR) expression in patient tissue samples identified a 2.7‐fold reduction in AR expression ( p  < 0.005) in papillary thyroid cancer compared with matched, normal tissue. An in vitro cell model was developed by stably transfecting AR into 8505C undifferentiated thyroid cancer cells (resulting in clone 84E7). The addition of DHT to the clone 84E7 resulted in AR translocation into the nucleus and a 70% reduction in proliferation, with a shift in the cell cycle toward G1 arrest. RNASeq analysis revealed significant changes in mRNA levels associated with proliferation, cell cycle, and cell cycle regulation. Furthermore, androgen significantly decreased the levels of the G1‐associated cell cycle progression proteins cdc25a CDK6 CDK4 and CDK2 as well as increased the levels of the cell cycle inhibitors, p27 and p21. The data strongly suggest that DHT induces a G1 arrest in androgen‐responsive thyroid cancer cells. Together, these data support our hypothesis that AR/androgen may play a protective, antiproliferative role and are consistent with younger men having a lower incidence of thyroid cancer than women. Abstract :